2019
DOI: 10.1002/cssc.201802960
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Micro‐Mesoporosity for Activity Maximization of N‐Doped Carbonaceous Electrocatalysts for the Oxygen Reduction Reaction

Abstract: Supporting Information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 50 publications
2
43
0
Order By: Relevance
“…Besides, higher total porosity significantly improves the ORR activity. 95 As for the M-N-C catalyst, there should also be a balanced ratio of micropore to mesopore, even macropore. 96 As shown in Figure 9B, in addition to Fe%, the representative Fe-N-C catalyst presents the dependent ORR activity on the ratio of micropore to mesopore.…”
Section: Engineering Of Porous Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, higher total porosity significantly improves the ORR activity. 95 As for the M-N-C catalyst, there should also be a balanced ratio of micropore to mesopore, even macropore. 96 As shown in Figure 9B, in addition to Fe%, the representative Fe-N-C catalyst presents the dependent ORR activity on the ratio of micropore to mesopore.…”
Section: Engineering Of Porous Structuresmentioning
confidence: 99%
“…95 Reproduced with permission: Copyright 2019, Wiley. 95 B, Relationships among the kinetics current density at 0.9 V, Fe content, and the ratio of micropore/mesopore. 97 Reproduced with permission: Copyright 2017, American Chemical Society 97 F I G U R E 1 0 An overview of biological materials, the biomass, demonstrating a wide range in length scales and structures according to their critical dimensions.…”
Section: Artificial Porous Structure Derived From Biomass Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Doping carbons with electron‐deficient boron would favor the adsorption of O 2 in the boron dopant [20–22] . Different types of nitrogen‐doped carbons have been proven to benefit ORR performance [23–25] . Relevant research on B and N co‐doped carbon materials as ORR catalysts has been reported [26–28] …”
Section: Introductionmentioning
confidence: 99%